Making Liquid Organic Fertilizer from Gamal Leaves in Iloheluma Village, Patilanggio District, Gorontalo - Ria Megasari; Erse Drawana Pertiwi; Muhammad Nasrul; Muh Arsyad; Yulan Ismail; Irwan Nooyo (Fakultas Sains Dan Teknologi, Universitas Muhammadiyah Sidenreng Rappang, 2026)
This community service activity was carried out in Iloheluma Village, Patilanggio District, Pohuwato Regency, Gorontalo, aiming to enhance farmers’ knowledge and skills in utilizing local resources particularly Gliricidia sepium leaves as raw material for producing liquid organic fertilizer (LOF). The program employed counseling, hands-on training, and mentoring methods during the preparation and application of LOF in agricultural fields. The results indicated a significant improvement in participants’ understanding of organic farming concepts and their ability to independently produce and apply LOF. Moreover, the use of G. sepium leaves proved to be efficient, cost-effective, and environmentally friendly, offering a sustainable alternative to chemical fertilizers. This program is expected to strengthen farmers’ self-reliance in organic fertilizer production and promote the sustainability of local agricultural systems.